26th International Conference on Indium Phosphide and Related Materials (IPRM) 2014
DOI: 10.1109/iciprm.2014.6880525
|View full text |Cite
|
Sign up to set email alerts
|

Resonant-tunneling-diodeterahertz oscillator integrated with slot-coupled patch antenna

Abstract: Short-Abstract-We proposed and fabricated resonanttunneling-diode (RTD) terahertz oscillators integrated with slotcoupled patch antennas for extraction of output power without the use of Si lenses. By eliminating a usually used bulky Si lens, we obtained a compact room-temperature terahertz oscillator. A 170-m square patch antenna was fabricated on a 7-m-thick BCB layer stacked on an RTD with a slot resonator. The RTD oscillated at 500 GHz, and the output power of ~40 W was radiated in the upward direction at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…So far, the achieved output power is in the order of 1 mW at 300 GHz for UTC-PDs. Therefore, THz UTC-PD sources, integrated with antennas, are still at a research level, although some prototypes have been successfully demonstrated [10][11][12][13].…”
Section: Beam Forming Conceptmentioning
confidence: 99%
“…So far, the achieved output power is in the order of 1 mW at 300 GHz for UTC-PDs. Therefore, THz UTC-PD sources, integrated with antennas, are still at a research level, although some prototypes have been successfully demonstrated [10][11][12][13].…”
Section: Beam Forming Conceptmentioning
confidence: 99%
“…The stacking approach enhances the upward radiation. A THz-enabled antenna is proposed in [76], and shows that an efficient power coupling between the antenna and source, results in a considerable improvement in the performance of the antenna. Moreover, the layering concept is used in [77] to build up a simple printed Yagi-Uda antenna, which uses two different substrates, i.e.…”
Section: A Basic Thz Antenna Designmentioning
confidence: 99%
“…For antenna dimensions of a few microns (at THz frequencies), proper impedance matching for this antenna is difficult. The planar horn antenna, on the other hand, radiates the signal energy along the substrate, whilst radiation perpendicular to the substrate would be more desirable [8]. An elevated patch antenna was proposed to suppress the substrate effects, however, the bandwidth still narrow [9].…”
Section: Introductionmentioning
confidence: 99%